2017
DOI: 10.1039/c7cp04619g
|View full text |Cite
|
Sign up to set email alerts
|

Proton conduction in alkali metal ion-exchanged porous ionic crystals

Abstract: Proton conduction in alkali metal ion-exchanged porous ionic crystals A[CrO(OOCH)(etpy)][α-SiWO]·nHO [I-A] (A = Li, Na, K, Cs, etpy = 4-ethylpyridine) is investigated. Single crystal and powder X-ray diffraction measurements show that I-A possesses analogous one-dimensional channels where alkali metal ions (A) and water of crystallization exist. Impedance spectroscopy and water diffusion measurements of I-A show that proton conductivities are low (10-10 S cm) under low relative humidity (RH), and protons mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…On the other hand, the band extended toward the higher frequency (wavenumber) (3500-3600 cm −1 ) for I and II, and also toward the lower frequency (3200 cm −1 ) for I. Previous reports by us and other groups have shown that the bands at high (3500-3600 cm −1 ) and low (3200-3400 cm −1 ) frequencies can be attributed to unperturbed (free) water molecules at the outside of a water cluster and to perturbed hydrogen-bonded water molecules inside the cluster, respectively 41,42 . Therefore, it can be reasonably stated that I possesses an extensive hydrogen-bonding network of water molecules and PAA, which agrees with the relatively large number of the water of crystallization (19 (I) > 16 (II), 15 (III)), and free water molecules (protons) at the periphery of the hydrogen-bonding network.…”
Section: Resultsmentioning
confidence: 74%
“…On the other hand, the band extended toward the higher frequency (wavenumber) (3500-3600 cm −1 ) for I and II, and also toward the lower frequency (3200 cm −1 ) for I. Previous reports by us and other groups have shown that the bands at high (3500-3600 cm −1 ) and low (3200-3400 cm −1 ) frequencies can be attributed to unperturbed (free) water molecules at the outside of a water cluster and to perturbed hydrogen-bonded water molecules inside the cluster, respectively 41,42 . Therefore, it can be reasonably stated that I possesses an extensive hydrogen-bonding network of water molecules and PAA, which agrees with the relatively large number of the water of crystallization (19 (I) > 16 (II), 15 (III)), and free water molecules (protons) at the periphery of the hydrogen-bonding network.…”
Section: Resultsmentioning
confidence: 74%
“…2(c), the NH 4 + cations and the water molecules were in hydrogen-bonding distances with respect to each other [NÁ Á ÁOW = 2.62 (5) Å and OWÁ Á ÁOW = 2.76 (4)-3.24 (5) Å , where OW is the O atom of a water of crystallization]. The distances were shorter than those in I-Cs + [CsÁ Á ÁOW = 2.91 (2)-3.45 (4) Å and OWÁ Á ÁOW = 2.92 (3)-3.14 (4) Å ; Uchida et al, 2017], suggesting that the dense hydrogen-bonding network in I-NH 4 + would contribute to efficient proton conduction (see below). Nyquist plots of the impedance spectra of a pelleted sample of I-NH 4 + were measured at 303-363 K and RH95% (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…SXRD analysis of I-NH 4 + showed that one-dimensional channels with a minimum aperture of 3.5 Å , which are analogous to those of I-A + (Uchida et al, 2017), existed along the c axis (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations